PENAMBAHAN TEPUNG PORANG SEBAGAI ALTERNATIF PENGGANTI BAHAN PENGENYAL SINTETIS PADA PRODUK BAKSO IKAN KURISI: The addition of Porang Flour as an Alternative to Synthetic Gelling Agents in Kurisi Fish Balls Products - Novia Rahayu; Meydia Kusuma Wardani; Agustono Prarudiyanto; Zainuri Zainuri (Pro Food, 2023)
Meatballs are a popular processed food product made primarily from beef, enjoyed by individuals across various age groups. In addition to beef, fish meat can also be used as a raw material for meatballs. However, the conventional production of meatballs often involves the utilization of synthetic gelling agents that pose potential health risks to consumers. This study aimed to assess the chemical, physical, and organoleptic attributes of kurisi fish balls fortified with porang flour (Amorphophallus oncophillus) as a substitute for synthetic gelling agents..  The research method used was a Group Randomized Design (RAK) comprising six treatment groups with varying proportions of porang flour 0%, 1%, 2%, 3%, 4%, and 5%  with  3 replication. Analysis of variance (ANOVA) at a 5% significance level was conducted using Co-stat software to evaluate the data, followed by Polynomial Orthogonal tests to assess chemical and physical quality parameters. Organoleptic quality was evaluated using the Honestly Significant Difference test (BNJ). The findings indicated that the addition of porang flour significantly influenced water content, ash content, protein content, as well as chewiness, color, and texture assessed hedonically. However, taste and aroma were not significantly affected. Based on the results of chemical and organoleptic analysis, the best treatment of kurisi fish balls in this study was the addition of porang flour concentration by 3%, having water content (70.25%), ash content (1.54%), protein content (15.27%) and organoleptic favored by panelists.